O papel dos bancos públicos na concessão de crédito para os pequenos negócios brasileiros durante a pandemia Covid-19 - Pereira, Daiane Sales (2021)
The work aims to analyze the granting of credit to small businesses during the COVID-19 Pandemic and to verify the role of public banks in the implementation of public policies to deal with the installed crisis. To achieve this objective, a descriptive and quantitative analysis was carried out, using data provided by the Central Bank of Brazil and the Brazilian Micro and Small Business Support Service. The analysis made it possible to verify the relationship between variables such as credit granting, average interest rate, default rate and balance in the portfolio, in addition to verifying the cause-and-effect relationship between them. It was found that during the pandemic period there was an increase in the volume of credit, including for the segment of micro and small companies, the effect of the credit programs created by the federal government. Although the resources of the programs were destined to the broadest segment of the economy and the most susceptible to crises, the volume was not enough to meet the great demand. In this context, public banks were the protagonists, being the largest grantors of the resources allocated by the programs, demonstrating the importance of the performance of public banks as executors of government public policies.